The limits of collective humanitarian securitization : the case of EU policy on the Syrian refugee crisis - Szucs, Bettina (2018)
This dissertation seeks to reveal the limits of the European Union's (EU) attempt to securing human life during the Syrian Refugee Crisis. It does so by using literature on the concept of securitization to explore the dynamics through which the European Union (EU) is dealing with the present crisis. After providing an overview of the Copenhagen School's (CS) main arguments and central critiques, it demonstrates how the securitization framework can be applied to regional organisations where states collectively undertake securitization. In addition, it treats humanitarianism as a distinct sector of securitization in order to understand how the 'human' as a referent object has the ability to legitimise emergency measures. It concludes that the European Union's attempt to collectively securitize the 'human' in the Syrian Refugee Crisis was successful. However, this success was achieved primarily outside the borders of the EU and attempts to replicate such aims within the EU borders were met with some limitations as a result of the lack of consensus of the organisation's member states on how to address the crisis.